A COVID-19 Ringan Pada Tenaga Medis: Evaluasi Temuan Klinis dan Risiko Transmisi - Mahrani; Hana Khairina Putri Faisal; Paramita Khairan; Iﬀa Mutmainah; Fitriana Nur Rahmawati; Sarah Shafa Marwadhani; Gadistya Novitri Adinda; Uti Sari; Pukovisa Prawirohardjo (Majalah Kedokteran Indonesia, 2020)
Objective: Since December 2019, COVID-19 has become a global concern causing more than thousands of deaths worldwide. The major challenge in fighting against this new emerging disease is the limited data regarding the heterogeneity of its clinical and epidemiological features. We aim to fill this knowledge gap by evaluating a mild case of COVID-19 infecting a health worker in Indonesia.Method: We report a 31-year-old male doctor who was hospitalized for mild pneumonia with positive SARS-CoV-2 swab testResult: This case presents an estimated incubation period of 2 days. The patient showed mild upper respiratory symptoms without significant pneumonia symptoms, however mild pneumonia was confirmed by the presence of fever and pulmonary infiltrates on imaging. Despite the seemingly mild symptoms, there was a complex systemic reaction as thrombocytopenia and elevated aminotransferase enzyme occurred. The patient is a health worker susceptible to SARS-CoV-2 transmission with a close contact history with a suspected COVID-19 patient, without wearing an adequate personal protective equipment (PPE).Conclusion: Patients with mild presentation of COVID-19 could exhibit a complex systemic reaction and organ injury. The use of an appropriate PPE among health workers is crucial to prevent patient-to-doctor transmission.